Chip-integrated polarization multiplexed metasurface for simultaneous generation of versatile terahertz vortices - Zhang Qianyun; Li Guibin; Wu Liang; Yang Fan; Yue Zhen; Zheng Chenglong; Zhang Yan; Li Li; Yao Jianquan (Nanophotonics)
Terahertz vortex beams, carrying orbital angular momentum (OAM), are quite desirable for enhancing data transmission capability in telecommunication. However, it faces fundamental and technical challenges in a single metasurface to simultaneously generate orthogonal basis vortices with linear polarization (x- and y-polarity) and circular polarization (left- and right-handed polarity) under the orthogonal polarized light incident. Here, we proposed a chip-integrated all-dielectric metasurface in the terahertz regime, to demonstrate the simultaneous generation of four-channel orthogonal polarized vortex beams at various topological charges under the x- and y-polarized light incident. The polarization multiplexed metasurface was designed only with a propagation phase strategy, consisting of polarization-maintaining and polarization-conversion meta-atoms. Simultaneous control of polarization and topological charges in vortex beams was realized by properly arranging birefringent meta-atom arrays to induce additional phases of x- and y-polarization as customized, showing more degrees of freedom for carrying information. The experimental results are in good agreement with the simulations. Such a metasurface approach provides complete polarization bases for further synthesis of diverse polarization vortices required for huge-capacity communication.